Corrosion behavior of stainless steels in simulated PWR primary water: The effect of composition and matrix phases. (December 2020) - Xiao, Qian; Jang, Changheui; Kim, Chaewon; Kim, Hyunmyung; Chen, Junjie; Lee, Hyeon Bae
Highlights: Cr-rich (Cr2 O3 +FeCr2 O4 ) inner oxide layer on stainless steels with 22 wt% Cr. Cr-rich spinel inner oxide layer on stainless steels with 16 wt% Cr. B2-NiAl phase is oxidized as (Fe, Ni, Al)3 O4 fine spinel oxides. Phases (ferrite, austenite and B2-NiAl) affect corrosion behavior in addition to chemical composition. Abstract: Corrosion behavior in simulated pressurized water reactor (PWR) primary water was investigated for stainless steels with 16 and 22 wt% Cr having austenitic, ferritic, and duplex microstructure. For alloys with 22 wt% Cr, the Cr-rich inner oxide layer consisted of Cr2 O3 and FeCr2 O4 is formed. For alloys with 16 wt% Cr, the Cr-rich spinel inner oxide layer is formed. In-situ and ex-situ electrochemical impedance analyses and Mott-Schottky analysis was used to rank the corrosion resistance of the alloys. In addition to chemical composition, the phases (ferrite, austenite, and B2-NiAl) also affect the corrosion behaviors of the alloys.